Understanding diabetes knowledge and awareness among the Hispanic/Latino population in San Antonio, Texas: implications for diabetes prevention interventions - Reyes Santa, Idalis (Kansas State University, 2024)
Objective: The purpose of this report is to address some of the gaps in the understanding of diabetes knowledge and awareness in the Hispanic/Latino population residing in San Antonio, Texas. The report focuses on various factors, including physiological, environmental, healthcare system access, and cultural factors that influence diabetes prevalence and management. Methods: A comprehensive literature review was conducted to gather data about diabetes knowledge and awareness on Hispanic/Latino populations in urban/suburban in the US. Sources for this report include peer-reviewed journal articles, community health information, and government health reports. Results: San Antonio is mostly comprised of Hispanic/Latino population. Findings revealed that compared to other race/ethnic groups; Hispanic/Latino populations are at increased risk of type 2 diabetes. It was also revealed that compared to Texas, the San Antonio area had a higher mortality rate for diabetes and higher diabetes-related amputations. Implications: Culturally interventions are required to target the specific needs of the Hispanic/Latino population in San Antonio, Texas. Recommendations include addressing language barriers, understanding cultural beliefs and family dynamics, promoting culturally competent healthcare that considers health literacy and education level, addressing physical inactivity and access to nutritious foods, and ways to effectively disseminate information to this specific population. Conclusion: This report emphasizes the importance of implementing multifaceted strategies to improve diabetes knowledge and awareness among Hispanic/Latino populations in San Antonio, Texas. Addressing different physiological, environmental, healthcare systems, and cultural factors could help improve diabetes knowledge and awareness in this population, thus improving diabetes outcomes and overall health.
Keywords: Diabetes; Hispanic; Latino; Awareness; San Antonio